THE MUTUAL-BENEFIT PARTNERSHIP MANAGEMENT MODEL FOR VOCATIONAL HIGH SCHOOLS AND WORK/INDUSTRY SECTOR - Sumaryanto Sumaryanto; Azhari Azhari; Sitepanus Zebua; Mursalin Mursalin; Kisno Kisno (Green Publisher, 2023)
This study aims to: (1) explore information related to the partnership management model currently in Vocational Schools (VHS); and (2) creating a partnership management model expected by the industry and work sector. The research method used was an instrumental case study. The subject of this research was VHS, and the industry and work sector and the data was collected through interviews, documentation, and observation. The data analysis technique used was ATLAS.ti 9 software and the validation was carried out by triangulation through Chief Section of Vocational School and the other related Vocational Schools. The results of the study indicated that (1) the partnership management model currently in Vocational Schools was still limited to planning, implementing, and evaluating students; and (2) the management model desired by the industry and work sector included guidelines for partnership, education and training standards, student guidance systems, skills testing standards, and student competency assessment standards. Therefore, it is essential that the government issue regulations or laws that bind the world of work in realizing the partnership between VHS and world of work. Then, schools should involve the world of work in collaborative management so that there is an integration between what the school expects and the results obtained by students. The world of work should help realize the role of VHS through a structured partnership programs aiming mutual benefit suitable to the needs of world of work